An exploration of the determinants of sexual risk behaviour among adolescent girls and young women aged 15-24 years in South Africa: a sub-study of the 2019-2022 HERStory2 study - Chamuka, Paidashe (Department of Public Health and Family Medicine, 2025)
Objective: The study aims to understand why South African adolescent girls and young women (AGYW) engage in sexual risk behaviours, such as unsafe sex and transactional and inter-generational sexual relationships. These behaviours lead to adverse sexual and reproductive health (SRH) outcomes, including HIV, STIs, unplanned pregnancies, and forced sex. By exploring the perspectives of AGYW and community stakeholders, the study seeks to enhance future interventions aimed at reducing the risk of STIs, including HIV, and unintended pregnancies among AGYW. Methods The study is based on the qualitative component of the HERStory2 study, a mixed-methods evaluation of an SRH intervention for AGYW in six South African districts. Data from in-depth interviews with twenty-seven participants were thematically analysed using the social-ecological model as a theoretical framework. Results The findings showed that the reasons for AGYW's engagement in sexual risk behaviour are nested within individual, interpersonal, community, and structural levels. At the individual level, participants reported that AGYW may engage in sexual risk behaviours due to their age, low perception of risk, problematic alcohol consumption, and the need for high grades at school. At the interpersonal level, social media-induced peer pressure was cited as a reason for AGYW's engagement in sexual risk behaviours. Community-level factors included lack of safety and economic activities such as mining. At the structural level, poverty, negative attitudes from public healthcare providers at clinics, and social and gender norms were perceived to influence AGYW's sexual risk behavior. Conclusion The results suggest that AGYW's sexual risk behaviour is influenced by many complex factors beyond the individual. The results call for targeted holistic interventions to reduce sexual risk behaviour and improve the SRH outcomes for AGYW in this high HIV burden context.